Multi-Body Simulation and Multi-Objective Optimization Applied to Vehicle Dynamics - Maggio Fabiano (International Journal for Simulation and Multidisciplinary Design Optimization, 2009)
This paper describes a demo application, where modeFRONTIER, a commercial software for design optimization, is coupled with a parametric 2D Multi-Body model of a touring motorcycle. The optimizer is asked to identify the characteristics of the front suspension (telelever scheme) that deliver more safety, more stability, and more riding comfort for a braking maneuver in straight running. All objectives are described through 4 scalar indexes, extracted from the braking kinematics. As expected, results highlight that trade-off relationships connect the objectives. Only 13, among the 1900 tested configura-tions, are able to simultaneously improve the 4 indexes. Moreover, no design in this selection assures a decisive improvement of the stability. In order to accomplish this priority requirement, the best design is chosen accepting a slight reduction of stabil-ity.